Occupations of graduates majoring in the division of agriculture of Colorado State College for the ten year-period, 1927-1936 - Woodul, Parker A., author; Mondart, Clifford L., advisor; Schmidt, Gustavus Adolphus, 1880-, committee member; Aspinwall, Lloyd E., committee member; Durrell, L. W. (Lawrence Wood), 1888-1970, committee member (Colorado State University. Libraries, 1940)
To view the abstract, please see the full text of the document.
Keywords: Colorado A & M College -- Alumni and alumnae; Agricultural education -- Colorado